Pelvic ultrasounds referred from the emergency department: Agreement between sonographer findings and radiologists' reports. Issue 1 (20th December 2020) - Kolsky, Ellen; Baker, Tim; Pontonio, Luke; Kelson, Tamika; Schneider, Michal
Abstract: Introduction: When radiologists are not available, sonographers may be able to provide an interim report, especially for patients referred from emergency or in remote clinics. The aim of this study was to compare the agreement of diagnostic findings between sonographers and radiologists for patients referred from the emergency department for pelvic ultrasound. Methods: Sonographer findings and corresponding radiologists' reports of consecutive pelvic ultrasound examinations referred from the emergency department were compared prospectively over a 7‐month period. Paediatric cases were excluded. Diagnostic agreement was scored by an independent investigator into the following: grade 1—agree with radiologist report; grade 2—minor discrepancy, unlikely to impact patient management; grade 3—major discrepancy, likely to impact patient management but does not lead to adverse outcomes for the patient; and grade 4—major discrepancy, findings likely to result in significantly adverse outcome for the patient. Results: A total of 118 cases were recruited. Of those, 113 (95.7%) were graded as grade 1, four (3.4%) were graded as grade 2 and one as grade 3 (0.8%). No cases were categorised as grade 4. The case classified as grade 3 was initially reported by the sonographer as early ovarian torsion. The corresponding radiologist's report documented no evidence of ovarian torsion. However, three days later, the woman underwent emergency surgery where ovarian torsion was confirmed and the ovary removed. Conclusion: When radiologists are unavailable to report on urgent cases requiring pelvic ultrasound, sonographers can provide accurate interim reports to assist in the timely management of patients.